Congruent population genetic structures and divergence histories in anther‐smut fungi and their host plants Silene italica and the Silene nutans species complex. Issue 6 (8th March 2020) - Hartmann, Fanny E.; Snirc, Alodie; Cornille, Amandine; Godé, Cécile; Touzet, Pascal; Van Rossum, Fabienne; Fournier, Elisabeth; Le Prieur, Stéphanie; Shykoff, Jacqui; Giraud, Tatiana
Abstract: Study of the congruence of population genetic structure between hosts and pathogens gives important insights into their shared phylogeographical and coevolutionary histories. We studied the population genetic structure of castrating anther‐smut fungi (genus Microbotryum ) and of their host plants, the Silene nutans species complex, and the morphologically and genetically closely related Silene italica, which can be found in sympatry. Phylogeographical population genetic structure related to persistence in separate glacial refugia has been recently revealed in the S. nutans plant species complex across Western Europe, identifying several distinct lineages. We genotyped 171 associated plant–pathogen pairs of anther‐smut fungi and their host plant individuals using microsatellite markers and plant chloroplastic single nucleotide polymorphisms. We found clear differentiation between fungal populations parasitizing S. nutans and S. italica plants. The population genetic structure of fungal strains parasitizing the S. nutans plant species complex mirrored the host plant genetic structure, suggesting that the pathogen was isolated in glacial refugia together with its host and/or that it has specialized on the plant genetic lineages. Using random forest approximate Bayesian computation (ABC‐RF), we found that the divergence history of the fungal lineages on S. nutans was congruent with that previously inferred for the host plant and probably occurred with ancient but no recent gene flow. Genome sequences confirmed the genetic structure and the absence of recent gene flow between fungal genetic lineages. Our analyses of individual host–pathogen pairs contribute to a better understanding of co‐evolutionary histories between hosts and pathogens in natural ecosystems, in which such studies remain scarce.